2009
DOI: 10.1149/1.3028218
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Dielectric Properties of SrTiO[sub 3] Films with a SrRuO[sub 3] Seed by Plasma-Enhanced Atomic Layer Deposition

Abstract: The dielectric properties of SrTiO 3 thin films deposited on SrRuO 3 seed layer were investigated. The SrTiO 3 thin films were deposited by plasma-enhanced atomic layer deposition using Sr͑C 11 H 19 O 2 ͒ 2 and Ti͑O i -C 3 H 7 ͒ 4 as precursors and O 2 plasma as an oxidant. The SrRuO 3 seed layer was formed through deposition of an SrO layer on a RuO 2 substrate and postannealing in O 2 ambient. As a result of introducing SrRuO 3 seed layers, the dielectric constant of 10 nm thick SrTiO 3 thin films increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…To maintain the required cell capacitance (25-30 fF/cell) in dynamic random access memory (DRAM) with design rules of 45 nm or less, high-k dielectric materials, such as ZrO 2 , TiO 2 , Ta 2 O 5 , SrTiO 3 , and (Ba,Sr)TiO 3 , have been extensively investigated. [1][2][3][4][5][6][7][8][9] For this application to be successful, the choice of a suitable capacitor electrode material is very important. The capacitor electrode material should not react with oxygen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To maintain the required cell capacitance (25-30 fF/cell) in dynamic random access memory (DRAM) with design rules of 45 nm or less, high-k dielectric materials, such as ZrO 2 , TiO 2 , Ta 2 O 5 , SrTiO 3 , and (Ba,Sr)TiO 3 , have been extensively investigated. [1][2][3][4][5][6][7][8][9] For this application to be successful, the choice of a suitable capacitor electrode material is very important. The capacitor electrode material should not react with oxygen.…”
mentioning
confidence: 99%
“…The noble metals, such as Pt and Ru, are preferentially considered for use as electrode materials. [6][7][8][9][10][11][12] In addition to high work functions, these noble metals have sufficiently low resistivities that ultrathin films can be employed. Furthermore, these noble metals are able to minimize the device's leakage current, and they appear to have better chemical compatibility with the dielectrics than more conventional capacitor electrode materials such as TiN.…”
mentioning
confidence: 99%
“…94 Meanwhile, Ahn et al reported that a 2.7 nm SrO seed layer on RuO 2 annealed at 600 1C is optimal for obtaining the maximum k for main STO film (B160) compared to that of k = 85 and 91 for films deposited directly on Ru and via seeds formed on the Ru substrate, respectively. 88 Menou et al used a 5 nm STO seed layer annealed at 700 1C for 2 min with a Levitor tool. They reported that using a seed layer lowers the annealing temperature of the main STO layer for crystallization, which is beneficial for preventing oxidation in TiN bottom electrodes.…”
Section: Seed Layer Schemementioning
confidence: 99%